Analysis of Ability and Motivation in Improving the Performance of Cooperative Managers of Republic of Indonesia Employees in Palu City - Nur Hilal; Hariyanto R. Djatola (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The Law on Cooperatives emphasizes the strategic role of cooperatives in creating a just, prosperous, and prosperous society. Cooperatives are considered to be able to function as the backbone of the national economy as well as to grow and develop the people's economic potential and realize a democratic, economic life that is characterized by democracy, autonomy, participation, openness, and a social character (togetherness and kinship). Performance is related to absenteeism, work morale, complaints, or vital agency problems. Managers are one of the most important production factors in a cooperative. How difficult would it be for the Republic of Indonesia Employee Cooperative (KPRI) to achieve its goals? They are the ones who determine the progress and decline of the Republic of Indonesia Employee Cooperative (KPRI) by having skilled workers with high motivation. The Republic of Indonesia Employee Cooperative (KPRI) has costly assets because humans are the subject and object of development, which is a significant factor, especially since improving the quality of human resources is the main priority. This research aims to determine and analyze the abilities, motivation, and performance of the Republic of Indonesia Employee Cooperative Managers in Palu City. This research is descriptive. Questionnaires were distributed to 45 people managing the Republic of Indonesia Employee Cooperative in Palu City. The analytical tool used in this research is descriptive analysis. Based on the study and discussion, the ability, motivation, and performance of the Republic of Indonesia Employee Cooperative Managers in Palu City are excellent.